GAMBARAN PERILAKU SELF CARE MANAGEMENT PADA PENDERITA DIABETES MELITUS TIPE 2 (Studi di Wilayah Kerja Puskesmas Rowosari Kota Semaran Tahun 2018) - Hari Istiyawanti; Ari Udiyono; Praba Ginandjar; M. Sakundarno Adi (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2019)
Diabetes mellitus (DM) type 2 is a chronic disease characterized by an increase in glucose in the blood and can cause various complications. Complications of type 2 diabetes can be minimized through management efforts called diabetes self-care management. The purpose of this study was to describe the behavior of self-care management of diabetes in type 2 DM patients. This type of research was observational analytic research with a cross sectional research design. The results of this study indicate the average score of self-care management of respondents in this study was 52.13 with a range of scores from 0 to 119. On average respondents made dietary arrangements of 3.1 days in the last seven days. The average respondent did 3.5 days of physical exercise in the last seven days. The average respondent carries out 2.0 days of foot care in the last seven days. The average respondent did 5.3 days of treatment in the last seven days. The average respondent monitors blood glucose levels as much as 1.2 days in the last seven days. Based on the results of these studies indicate that the behavior of self care management in patients with type 2 DM has not been done optimally. Patients with type 2 DM are advised to apply diabetes self care management behavior routinely in their daily lives. Diabetes self-care management behavior that is routinely carried out can control the patient's blood glucose levels so that it can minimize the risk of complications due to type 2 diabetes.